Engineering InAs quantum dot pairs: Tailoring structural and optical properties with GaAs and GaAsSb spacer layers - Abdelmajid Salhi (9178041) (2025)
We investigated the optical and structural properties of vertically coupled InAs/GaAs quantum dots (QDs) grown by molecular beam epitaxy (MBE) and separated by thin GaAs and GaAs0.94Sb0.06 spacer layers (SLs). Atomic force microscopy (AFM) analysis of uncapped samples revealed larger top-layer QDs (TQDs) than seed-layer QDs (SQDs), regardless of the presence of Sb in the thin GaAs SL. Scanning transmission electron microscopy (STEM) confirmed the formation of InAs/GaAs and InAs/GaAsSb QD pairs. With a pure GaAs SL, TQDs were larger than SQDs, as expected. However, Sb incorporation into the GaAs SL increased the size of SQDs, leading to QD pairs with nearly identical dimensions. Power-dependent photoluminescence (PL) at 77 K revealed dual-layer (SQDs and TQDs) contributions to the first two emission peaks in both samples. Notably, while the lowest-energy emission originated from the TQDs in the sample with GaAs SL, it arose from the SQDs in the sample with GaAsSb SL. Additionally, the GaAsSb SL enhanced the PL intensity. Thermal activation energy analysis showed higher activation energies for the SQDs compared to the TQDs, consistent with the energy difference between the SQD emission and the wetting layer. The TQDs exhibited an activation energy of 120 meV in both samples, consistent with carrier escape from the TQDs into nonradiative recombination centers within the GaAs cap layer. These findings demonstrate that Sb incorporation into the GaAs SL enables precise control over the electronic and optical properties of artificial quantum dot (QD) molecules, offering a promising pathway for their integration into high-performance optoelectronic and quantum nanodevices. Other Information Published in: Optical Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.optmat.2025.117500